A Survey of Techniques for Auditing EDP-Based Accounting Information Systems. - Cash, James I.; Bailey, Andrew D.; Whinston, Andrew B. (The Accounting Review, 1977)
Abstract ABSTRACT: The primary objective of this paper is to review the extant literature concerning auditing and EDP systems. We trace the flow of EDP-auditing development, note salient points of similarity and difference in techniques and relate these issues to the auditors' professional responsibilities. We hope that this will contribute to efficient consideration of the past literature by those developing an interest in auditing-EDP systems. We also hope that it will encourage efficient progress in the effort to develop new EDP-auditing research. With this in mind, we have included a short section on new approaches to EDP-auditing which presents information on systems design involvement, software standardization and formal system assertions.